Diurnal activity pattern of white-rumped vulture, Gyps bengalensis (Gmelin, 1788) in captivity during breeding season at Bangladesh National Zoo, Dhaka (Jahangirnagar University Journal of Biological Sciences, 2018)
Abstract not availableJahangirnagar University J. Biol. Sci. 7(1): 81-85, 2018 (June)